(untitled) (REMUNOM, 2024)
The increasing advance of agricultural areas poses a risk to ecological functions and biodiversity. The evolution of agricultural systems, in the case of Brazil, benefited medium and large producers, with the large mass of small family farmers being left out of the modernization process. The objective of this study was to describe the evolution of agricultural systems regarding the use of natural resources, aiming at understanding the process of agricultural modernization and its interaction with the ecological base. For this, a qualitative, descriptive and bibliographical research was carried out. The results showed that the longing for sustainable actions in the evolution of the agricultural systems did not occur due to the preservation of the natural resources but by the economic advance. It was also observed that to reach new models of agricultural production, which have viability under the socioeconomic and environmental aspects requires a sum of efforts of researchers and producers.